Asset maintenance as hidden investment among the poor and rich: Application to housing - Hernandez, Manuel A.; Trupkin, Danilo R. (Elsevier, 2021)
Substituting maintenance of existing fixed assets for investment in new assets, and thus affecting their depreciation, can play a major role in the economic decisions of low-income agents. We develop a theoretical framework that shows that poorer households, which generally face relatively higher adjustment (moving) costs and more credit constraints, will adjust their home maintenance decisions to a higher degree than richer households after an income change. We test our predictions using a panel of homeowners from the American Housing Survey for 1997-2011. We find that the income elasticity of maintenance is higher among low- versus high-income households and that the adjustment differences are more acute for permanent than for transitory income changes. For every dollar increase in the estimated permanent and transitory income, home maintenance expenses will increase by 5.2 and 2.9 cents in the lower income tertile and by zero and 0.5 cents in the upper tertile.